Distribution of virulence factors, antimicrobial resistance genes and phylogenetic relatedness among Shiga toxin-producing Escherichia coli serogroup O91 from human infections - Magdalena Nüesch-Inderbinen; Marc J.A. Stevens; Nicole Cernela; Andrea Müller; Michael Biggel; Roger Stephan (Elsevier, 2021)
Shiga toxin-producing Escherichia coli (STEC) belonging to the serogroup O91 are among the most common non-O157 STEC serogroups associated with human illness in Europe. This study aimed to analyse the virulence factors, antimicrobial resistance genes and phylogenetic relatedness among 48 clinical STEC O91 isolates collected during 2003-2019 in Switzerland. The isolates were subjected to whole genome sequencing using short-read sequencing technologies and a subset of isolates additionally to long-read sequencing. They belonged to O91:H10 (n=6), O91:H14 (n=40), and O91:H21 (n=2). Multilocus sequence typing showed that the O91:H10 isolates all belonged to sequence type (ST)641, while the O91:H14 isolates were assigned to ST33, ST9700, or were non-typeable. Both O91:H21 isolates belonged to ST442. Shiga toxin gene stx1a was the most common Shiga toxin gene subtype among the isolates, followed by stx2b, stx2d and stx2a. All isolates were LEE-negative and carried one or two copies of the IrgA adhesin gene iha. In a subset of long-read sequenced isolates, modules of the Locus of Adhesion and Autoaggregation pathogenicity island (LAA-PAI) carrying iha and other genes such as hes, lesP or agn43 were identified. A large proportion of STEC O91:H14 carried the subtilase cytotoxin gene subA, colicin genes (cba, cea, cib and cma) or microcin genes (mcmA, mchB, mchC and mchF). STEC O91:H14 were further distinguished from STEC O91:H10/H21 by one or more virulence factors found in extraintestinal pathogenic E. coli (ExPEC), including hlyF, iucC/iutA, kpsE and traT. The hlyF gene was identified on a novel mosaic plasmid that was unrelated to hlyF+ plasmids described previously in STEC. Core genome phylogenetic analysis revealed that STEC O91:H10 and STEC O91:H21 were clonally conserved, whereas STEC O91:H14 were clonally diverse. Among three STEC O91:H14 isolates, a number of resistance genes were identified, including genes that mediate resistance to aminoglycosides (aadA, aadA2, aadA9, aadA23, aph(3'')-Ib and aph(6)-Id), chloramphenicol (cmlA), sulphonamides (sul2 and sul3), and trimethoprim (drfA12). Our data contribute to understanding the genetic diversity and differing levels of virulence potential within the STEC O91 serogroup.